Multi-Element Analysis of Blood Samples in a Passerine Species: Excesses and Deficiencies of Trace Elements in an Urbanization Study - Bailly, Juliette; Faivre, Bruno; Bernard, Nadine; Sage, Mickaël; Crini, Nadia; Driget, Vincent; Garnier, Stéphane; Rieffel, Dominique; Scheifler, Renaud (Frontiers in Ecology and Evolution, 2017)
Urbanization is a growing phenomenon characterized by a complete restructuring of natural areas. In urban bird populations, a reduced offspring survival and body condition and an overall lower breeding success are often observed compared to populations inhabiting more natural habitats. Higher pollution levels and poorer quality of natural resources in cities are two environmental factors frequently mentioned in the literature to explain the differences between urban and non-urban populations. Pollution and poor quality of food may lead to an excess of non-essential elements such as Pb or Cd or to deficiencies of essential elements such as Cu or Zn, which may explain some of the impacts, notably on immunity, observed in urbanization studies. The present study compared the breeding parameters, brood body mass and condition, and haptoglobin levels, a marker of inflammatory immunity, in two urban and two forest populations of Great tits in Eastern France, together with a multi-element analysis (25 non-essential and essential trace elements) of blood samples from 13-day-old nestlings from the four populations. The concentration of NO2, a gaseous pollutant typical of urban pollution, was also measured. The NO2 concentrations were significantly higher in the urban areas, but no association with biological variables was detected. Non-essential metals were undetectable in the plasma of the birds from both habitats, except Pb, whose concentrations, however, did not differ between the urban and forest birds. A positive relationship was found between the plasmatic richness in essential elements (as assessed from the coordinates of the first axis of a PCA including 12 elements) and the average brood body mass and condition. We suggest that lower quality resources or/and a higher metabolic demand may be a causal mechanism for the reduced body condition often observed in urban bird nestlings. Finally, our exploratory study could promote more mechanistic experiments (e.g. supplementation) to explain the negative effect of urban conditions on bird populations.